2021
DOI: 10.3390/ma14154071
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoresis Structurization of PZT/PDMS Micro-Composite for Elastronic Function: Towards Dielectric and Piezoelectric Enhancement

Abstract: Piezoelectric materials have been used for decades in the field of sensors as transducers and energy harvesters. Among these, piezoelectric composites are emerging being extremely advantageous in terms of production, costs, and versatility. However, the piezoelectric performances of a composite with randomly dispersed filler are not comparable with bulk ferroelectric ceramics and electroactive polymers. In order to achieve highly performing and low-cost materials, this work aims to develop flexible composites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Such an enhancement will allow lowering the input voltage subjected to the haptic device while maintaining its deformation beyond the detection threshold of human skin. To achieve this, improvements of the process via material structuration [ 93 , 94 ], together with an increase in the filler concentration and the use of highly anisotropic fillers (e.g., rod or wire shape instead of spherical [ 69 ]), are envisaged. As the conception of a haptic system strongly depends on its geometry and mechanical properties, another perspective of this work involves the development of design guidelines for vibration feedback regarding changes in the dimensions and architecture of the device.…”
Section: Discussionmentioning
confidence: 99%
“…Such an enhancement will allow lowering the input voltage subjected to the haptic device while maintaining its deformation beyond the detection threshold of human skin. To achieve this, improvements of the process via material structuration [ 93 , 94 ], together with an increase in the filler concentration and the use of highly anisotropic fillers (e.g., rod or wire shape instead of spherical [ 69 ]), are envisaged. As the conception of a haptic system strongly depends on its geometry and mechanical properties, another perspective of this work involves the development of design guidelines for vibration feedback regarding changes in the dimensions and architecture of the device.…”
Section: Discussionmentioning
confidence: 99%
“…In order to highlight the inherent potential of the structured thermoplastic piezoelectric composites developed in this study, it was necessary to thoroughly compare them to existing piezoelectric materials found in the literature [ 10 , 60 , 61 , 62 , 63 ]. This comparison was based on selected intrinsic properties, relevant to the development of a high-performance piezoelectric material, such as the piezoelectric voltage/charge coefficients, the density ( ρ ) and Young’s modulus ( Y ).…”
Section: Resultsmentioning
confidence: 99%
“…D'Ambrogio et al reported the fabrication of 1-3 PZT/polydimethylsiloxane (PDMS) composites from 0 to 3 composites by dielectrophoresis. 137 The piezoelectric response was higher for the 1-3 structured composite because of the arrangement in columns of particles (size 3.8 μm).…”
Section: The Case Of 1-3 Compositesmentioning
confidence: 97%
“…They measured piezoelectric coefficients ( d 31 ) of 14.8 pC/N for the highly oriented films, 10.8 pC/N for the poorly oriented ones, and 11.4 pC/N for the spherical particles composite after poling under an electric field of 1 kV/cm in the same direction as the induced orientation of the fibers (1‐direction). D'Ambrogio et al reported the fabrication of 1–3 PZT/polydimethylsiloxane (PDMS) composites from 0 to 3 composites by dielectrophoresis 137 . The piezoelectric response was higher for the 1–3 structured composite because of the arrangement in columns of particles (size 3.8 μm).…”
Section: Ceramic/fluorinated Polymer Compositesmentioning
confidence: 99%